Distribution of calcium-binding proteins immunoreactivity in the bottlenose dolphin entorhinal cortex - Graïc, Jean-Marie; Grandis, Annamaria; Sacchini, Simona; Tagliavia, Claudio; Salamanca, Giulia; Cozzi, Bruno; Bombardi, Cristiano (Frontiers in Neuroanatomy, 2024)
Introduction The entorhinal cortex has been shown to be involved in high-level cognitive functions in terrestrial mammals. It can be divided into two main areas: the lateral entorhinal area (LEA) and the medial entorhinal area (MEA). Understanding of its structural organization in cetaceans is particularly important given the extensive evidence for their cognitive abilities. The present study describes the cytoarchitectural and immunohistochemical properties of the entorhinal cortex of the bottlenose dolphin (Tursiops truncatus, Montagu, 1821), perhaps the most studied cetacean species and a paradigm for dolphins and other small cetaceans. Methods Four bottlenose dolphins’ entorhinal cortices were processed. To obtain a precise overview of the organization of the entorhinal cortex we used thionin staining to study its laminar and regional organization, and immunoperoxidase technique to investigate the immunohistochemical distribution of three most commonly used calcium-binding proteins (CBPs), calbindin D-28k (CB), calretinin (CR) and parvalbumin (PV). Entorhinal cortex layers thickness were measured, morphological and morphometric analysis for each layer were conducted and statistically compared. Results Six layers in both the LEA and MEA were identified. The main difference between the LEA and the MEA is observed in layers II and III: the neurons in layer II of the LEA were denser and larger than the neurons in layer II of MEA. In addition, a relatively cell-free zone between layers II and III in LEA, but not in MEA, was observed. The immunohistochemical distribution of the three CBPs, CB, CR and PV were distinct in each layer. The immunostaining pattern of CR, on one side, and CB/PV, on the other side, appeared to be distributed in a complementary manner. PV and CB immunostaining was particularly evident in layers II and III, whereas CR immunoreactive neurons were distributed throughout all layers, especially in layers V and VI. Immunoreactivity was expressed by neurons belonging to different morphological classes: All CBPs were expressed in non-pyramidal neurons, but CB and CR were also found in pyramidal neurons. Discussion The morphological characteristics of pyramidal and non-pyramidal neurons in the dolphin entorhinal cortex are similar to those described in the entorhinal cortex of other species, including primates and rodents. Interestingly, in primates, rodents, and dolphins, most of the CBP-containing neurons are found in the superficial layers, but the large CR-ir neurons are also abundant in the deep layers. Layers II and III of the entorhinal cortex contain neurons that give rise to the perforant pathway, which conveys most of the cortical information to the hippocampal formation. From the hippocampal formation, reciprocal projections are directed back to the deep layer of the entorhinal cortex, which distributes the information to the neocortex and subcortical area. Our data reveal that in the dolphin entorhinal cortex, the three major CBPs label morphologically heterogeneous groups of neurons that may be involved in the information flow between entorhinal input and output pathways.